A comparison of disease susceptibility and innate immune response between diploid and triploid Atlantic salmon (Salmo salar) siblings following experimental infection with Neoparamoeba perurans, causative agent of amoebic gill disease - Chalmers, Lynn; Taylor, John; Roy, William; Preston, Andrew Cree; Migaud, Herve; Adams, Alexandra (Parasitology, 2017)
Few studies have focussed on the health and immunity of triploid Atlantic salmon and therefore much is still unknown about their response to commercially significant pathogens. This is important if triploid stocks are to be considered for full-scale commercial production. This study aimed to investigate and compare the response of triploid and diploid Atlantic salmon to an experimental challenge with Neoparamoeba perurans, causative agent of amoebic gill disease (AGD). This disease is economically significant for the aquaculture industry. The results indicated that ploidy had no significant effect on gross gill score or gill filaments affected, while infection and time had significant effects. Ploidy, infection and time did not affect complement or anti-protease activities. Ploidy had a significant effect on lysozyme activity at 21 days post-infection (while infection and time did not), although activity was within the ranges previously recorded for salmonids. Stock did not significantly affect any of the parameters measured. Based on the study results, it can be suggested that ploidy does not affect the manifestation or severity of AGD pathology or the serum innate immune response. Additionally, the serum immune response of diploid and triploid Atlantic salmon may not be significantly affected by amoebic gill disease.